Descoberta Dinâmica de Serviços de IoT Baseado no Processamento Semântico de Fluxos de Eventos - Costa, Anderson Soares; Alves, Rodolfo Sobreira; da Silva e Silva, Francisco José; Endler, Markus (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2019)
The Internet of Things (IoT) is a combination of ubiquitous computing and the Internet, in which IoT (smart objects) devices can collect and exchange data, cooperating with people and the environment in which they find themselves. The Internet of Mobile Thing (IoMT), which is an extension of IoT, proposes scenarios in which smart objects and gateways are mobile. In this context, this work is focused on the discovery of smart objects in IoT/IoMT environments considering the following problems: mobility of both smart objects and gateways; great heterogeneity of smart objects and communication technologies to access them; the need for interoperability in these environments; the need to combine data from smart objects with knowledge bases. Therefore, the objective of this work is to combine Semantic Flow Processing with knowledge representation techniques to enrich the instantaneous and continuous discovery of smart objects and their services in IoT/IoMT environments. To this end, an ontology was developed to describe IoT/IoMT scenarios, a semantic middleware, an API for building information systems and applications, and a cloud infrastructure for querying and semantic streaming of smart objects. The evaluation of this work is done through a use case in the field of intelligent parking lots.